Tumoral calcinosis simulating sarcoma - S.V.R., Raja Sekhar; M., Shamili; B., Gouthami; Ch., Asha Latha; G., Harshitha (Tropical Journal of Pathology and Microbiology, 2020)
Tumoral calcinosis is a rare clinical and pathological entity, characterized by deposition of calcium in different sites of human body particularly in peri-articular tissues. It incidence is usually seen in young adults as a slowly growing, painless, firm to bony hard mass. Asymptomatic when small in size but larger masses can cause pressure symptoms due to compression of surrounding tissues or restriction of mobility of the joints. It can be predicted by typical radiological findings with the help of serum calcium and phosphorus levels but is confirmed only by histopathological examination. Many times, it isn’t very easy to diagnose this condition preoperatively and can be mistaken as soft tissue sarcoma both clinically and radiologically. Subtyping of this lesion depends on serum calcium, phosphorus levels, family history and co-morbid conditions like chronic renal failure. Hemodialysis, hypervitaminosis-D, milk-alkali syndrome, hyperparathyroidism, etc are responsible for the secondary causes. Treatment modality depends on the subtype, which can be medical or by surgical intervention. The present study was a case of adolescent male with a slowly growing swelling over the right hip region for 4 years. There was no traumatic history or any significant family history. Serum calcium and phosphorus levels were within normal limits. Radiology showed well-demarcated lobulated solid-cystic mass swelling measuring 7.8x3.9x3.5cm suggestive of sarcoma. The tumor was excised and sent for histopathological examination. Grossly, it was a ovoid solid-cystic firm to hard mass, microscopy showed large areas of dystrophic calcification with cystic spaces surrounded by foreign body giant cell reaction. Correlating with history, clinical findings, biochemical findings, the diagnosis of primary normophosphatemic tumoral calcinosis was made.